2019
DOI: 10.1016/j.kint.2018.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Organelle crosstalk in the kidney

Abstract: Organelle damage can cause various kidney diseases. In particular, organelle stress such as decreased proteostatic activity in the endoplasmic reticulum (ER) and altered energy metabolism in mitochondria contribute to glomerular and tubulointerstitial damage, resulting in the progression and development of kidney diseases. The ER regulates protein quality control via the unfolded protein response (UPR) pathway. Pathogenic ER stress leads to dysregulation of this pathway, and a maladaptive UPR is highly deleter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 82 publications
0
64
0
Order By: Relevance
“…Interestingly, cardiac myocytes also do not express plasmalemmal BK channels, and NS11021 shows therapeutic efficacy against IR injury in these cells and in ex vivo models of cardiac IR [18,21,22]. Nevertheless, our studies did not rule out the possibility that NS11021 activates BK channels at other non-mitochondrial organelles considering that cross-talk between intracellular organelles is well recognized [69][70][71][72][73][74]. Indeed, BK channels have been discovered in many cellular organelles as is nicely reviewed by Sing et al [75].…”
Section: Ns11021 Protects Nrk Cells Against Cs + Rw-induced Mitochondmentioning
confidence: 77%
“…Interestingly, cardiac myocytes also do not express plasmalemmal BK channels, and NS11021 shows therapeutic efficacy against IR injury in these cells and in ex vivo models of cardiac IR [18,21,22]. Nevertheless, our studies did not rule out the possibility that NS11021 activates BK channels at other non-mitochondrial organelles considering that cross-talk between intracellular organelles is well recognized [69][70][71][72][73][74]. Indeed, BK channels have been discovered in many cellular organelles as is nicely reviewed by Sing et al [75].…”
Section: Ns11021 Protects Nrk Cells Against Cs + Rw-induced Mitochondmentioning
confidence: 77%
“…In addition, other findings revealed that ER stress is involved in AKI triggered by renal I/R injury and nephrotoxic drugs (Gallazzini and Pallet, 2018;Yan et al, 2018). Many studies have reported that ER stress could trigger inflammatory responses and regulate mitochondrial metabolic status through the UPR signaling pathway (Bronner et al, 2015;So, 2018;Gallazzini and Pallet, 2018;Inoue et al, 2019). However, whether ER stress is involved in the protective effect of FGF2 on AKI has not yet been fully clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the role of ER stress in the regulation of cell growth, cell migration, cell differentiation, and apoptosis has been confirmed. Many studies have shown the relationship between excessive activation of ER stress and various kidney diseases, including AKI, chronic kidney disease (CKD), glomerular disease, and diabetic nephropathy (Inoue et al, 2019). Apoptosis, a form of programed cell death characterized by DNA cleavage and nuclear condensation, has been observed and well recognized in AKI (Schumer et al, 1992;Linkermann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Peroxisome proliferator activated receptor gamma co-activator-1-α (PGC-1α), a mitochondrial biogenesis regulator, plays a pivotal role in proximal tubular recovery from acute kidney injury (AKI) by regulating nicotinamide adenine dinucleotide (NAD) biosynthesis 2 . Mitochondrial dysfunction in the proximal tubular cells after AKI results in the progression of chronic kidney disease (CKD) 3,4 .…”
Section: Organelle Damage and Stress Signaling Mitochondriamentioning
confidence: 99%